2020
DOI: 10.3390/w12092550
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Vineyard Afforestation on Soil Properties, Water Repellency and Near-Saturated Infiltration in the Little Carpathians Mountains

Abstract: Vineyards are a 7000-year-old land-use tradition and both management and abandonment have result in altered soil properties. These have a great effect on water resources and soil services, and this inspired our investigation into the effects of land-use and land-use change on soils in the Modra wine-growing region in South-western Slovakia. Ten topsoil samples were taken at each of the seven research sites (n = 70) on granite parent material in cultivated and afforested vineyards and original forest soils. Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…According to Poleno et al (2011), mull is the most favourable type of forest floor for the entry of water into the mineral soil. Hrabovský et al (2020) reported that the infiltration rate was significantly higher in vineyard soils (compared to afforested soils) and it increased over time in soils afforested with Q. petraea and C. betulus. Tesař et al (2004) reported the soil water content was higher in dwarf pine (peaty soil) com-pared to Norway spruce (or meadow).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Poleno et al (2011), mull is the most favourable type of forest floor for the entry of water into the mineral soil. Hrabovský et al (2020) reported that the infiltration rate was significantly higher in vineyard soils (compared to afforested soils) and it increased over time in soils afforested with Q. petraea and C. betulus. Tesař et al (2004) reported the soil water content was higher in dwarf pine (peaty soil) com-pared to Norway spruce (or meadow).…”
Section: Resultsmentioning
confidence: 99%
“…For example, increased values of interception and transpiration and reduced values of river and stream runoff etc. were reported by many authors (Jackson et al 2005); the effect of agricultural land afforestation on water infiltration was reported by Ilstedt et al (2007) and Hrabovský et al (2020). For example, Ilsted et al (2007) synthesised and discussed the effect of afforestation on infiltrability in the tropics; the authors reported the infiltration increased approximately three-fold after afforestation or using trees in agricultural fields.…”
mentioning
confidence: 98%
“…The SWR -Cox relation can be supported by the fact that SWR is induced by the hydrophobic and amphiphilic components of soil organic matter. Some authors (e.g., Buczko et al, 2002;Hrabovský et al, 2020;Zavala et al, 2009) found positive correlation between SWR and soil organic matter; other authors shown that quantity of soil organic matter alone could not fully explain the increase of SWR (Zema et al, 2021). Dinel et al (1990) found that the concentration of hydrophobic lipid compounds decreases with increasing efficiency of organic matter decomposition and Cesarano et al (2016) shown that litter incorporated into the soil can produce a variety of effects on SWR, ranging from a dramatic increase to a null effect depending on the considered litter type.…”
Section: Resultsmentioning
confidence: 99%
“…Afforestation is already an important part of the response to global change. Planting trees can reduce surface runoff [ 2 , 3 , 4 ] and improve soil porosity and water conductivity, thereby changing the infiltration rate [ 5 , 6 , 7 ]. For example, [ 8 ] reported that where natural runoff is 30% of precipitation, planting trees can reduce runoff by half or more.…”
Section: Introductionmentioning
confidence: 99%